2002
DOI: 10.1074/jbc.m107711200
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species as Downstream Mediators of Angiogenic Signaling by Vascular Endothelial Growth Factor Receptor-2/KDR

Abstract: Recent evidence shows the involvement of reactive oxygen species (ROS) in the mitogenic cascade initiated by the tyrosine kinase receptors of several growth factor peptides. We have asked whether also the vascular endothelial growth factor (VEGF) utilizes ROS as messenger intermediates downstream of the VEGF receptor-2 (VEGFR-2)/KDR receptor given that the proliferation of endothelial cells during neoangiogenesis is physiologically regulated by oxygen and likely by its derivative species. In porcine aortic end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
237
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(249 citation statements)
references
References 37 publications
7
237
2
3
Order By: Relevance
“…Recently, it has been observed that DPI can cause apoptosis in rat heart cultured cells via induction of mitochondrial superoxide production (38) and induces in rat pulmonary aortic endothelial cells the transcription of heme oxygenase-1, a gene very sensitive not only to hypoxia but also to oxidative stress (39). Furthermore, in porcine aortic endothelial cells DPI potentiated the generation of ROS, both basally and after stimulation with vascular endothelial growth factor (29). Our results could then provide an explanation to such observations, reporting a "paradoxical" induction of oxidative stress by DPI.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been observed that DPI can cause apoptosis in rat heart cultured cells via induction of mitochondrial superoxide production (38) and induces in rat pulmonary aortic endothelial cells the transcription of heme oxygenase-1, a gene very sensitive not only to hypoxia but also to oxidative stress (39). Furthermore, in porcine aortic endothelial cells DPI potentiated the generation of ROS, both basally and after stimulation with vascular endothelial growth factor (29). Our results could then provide an explanation to such observations, reporting a "paradoxical" induction of oxidative stress by DPI.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of ROS could occur through their contribution to HIF␣ stabilization (5, 33) and/or HIF␣-independent pathways, such as interacting with proteins involved in angiogenesis (11,49). To examine the involvement of HIF1␣ and HIF2␣ in the formation of HUVEC tubes under atmospheric conditions, we used an RNAi suppression approach.…”
Section: Ros Mediates Tubulogenesis Through Hif␣-independentmentioning
confidence: 99%
“…This is because radical formation is, in the first place, an essential component of cell metabolism, taking part in the catalysis of numerous enzymatic activities [2,11] and in the fine control of cell metabolism through the control local redox potential [11,12]. ROS can be induced, as second messenger, by cytokines, oncogenes, growth factors or hormones [11,[13][14][15][16]. ROS of external origin or resulting from some insult to the cells or from deviation of the usual metabolism of oxygen can mimic the effects of ROS induced as constitutive second messenger and can trigger activation of many transcription factors through the release of signaling proteins [11,17,18].…”
Section: Overview Of Radical Phenomenamentioning
confidence: 99%